IMPLEMENTASI EUGENETIKA SEBAGAI ALASAN ABORSI MENURUT PERSPEKTIF HUKUM ISLAM - Rahman, Harfiah; Daeng Materu, Ruslan; M.H, Mustafa (IAIN BONE, 2024)
This research discusses the concept of Eugenics, the factors that encourage the application of Eugenics as a reason for abortion, the impact of the application of Eugenics, as well as the view of Islamic law towards the application of eugenics as a reason for abortion. The research method used is qualitative using a normative and sociological approach. The data used in the research is secondary data sourced from primary legal materials and secondary legal materials. The research results show that the concept of eugenics is one of the reasons for the practice of abortion or termination of pregnancy to avoid the birth of babies with defects or genetic diseases. The justification for the practice of eugenics is to obtain normal offspring. Eugenics has an impact on the mother's physical and mental health. In Islam, a fetus is not yet fully categorized as a human being, but in some legal cases such as inheritance, Islam gives the right to the possibility of life. Because a fetus is the beginning of a living human being, a fetus that has been breathed into by God's spirit, then aborted, is considered haram by Islamic scholars. Meanwhile, in Islam there is no clear legal provision for aborting a fetus that has not been given a soul.